Association Between Child Abuse Experience and Pathological Internet Use Among Chinese University Students: The Mediating Roles of Security and Maladaptive Cognitions - Qin, Ningbo; Li, Pei; Tian, Yu (Frontiers in Psychology, 2022)
Research has revealed that child abuse experience can increase pathological Internet use; however, few studies have focused on the influence of child abuse experience on pathological Internet use. This study examined the mediating roles of security and maladaptive cognitions in the association between child abuse and pathological Internet use. A total of 918 Chinese university students participated in the study, with measurements of child abuse, security, maladaptive cognitions, and pathological Internet use being employed. Structural equation modeling results indicated that child abuse could positively predict (i) pathological Internet use, (ii) pathological Internet use through the mediating role of security, (iii) pathological Internet use through the mediating role of maladaptive cognitions, and (iv) pathological Internet use through the chain mediating role of security and maladaptive cognitions. These results indicated that security and maladaptive cognitions were the primary factors in the association between child abuse and pathological Internet use.